Sin and crime: an Islamic educational perspective - Abd Rashid, Adnan (The Institute of Islamic Understanding Malaysia, 2003)
Man's life is never morally neutral because he can be involved in either good or evil.This dual ability is deeply ingrained within him. Man may be driven to on of them either inner motives or outside influences.He has to recognise and distinguish between what is good and bad for him on the basis of his freewill and his intelligent. Therefore he who purifies himself with goodness will achieve a successful, and the reverse of that could happen if he chooses to corrupt himself. This article attempt to discuss the crucial point to be understood in the issue of crime in Islam is that no inherited tendencies bind in a man to become a criminal.Actually a criminal voluntarily follows his lust and this way of luring, which is schemed by shaitan, is direct cause of his involvement in sin and crime.